Physical activity and symmetry following total knee arthroplasty: Results of a pilot randomized trial - Robin M. Queen; Liubov Arbeeva; Daniel N. Bracey; Derek Hales; Carla Hill; Katie F. Huffman; Todd A. Schwartz; Kelli D. Allen (Osteoarthritis and Cartilage Open)
Objective: This pilot trial examined a Physical Activity and Symmetry (PAS) intervention focused on common deficits of physical inactivity and joint loading asymmetry following total knee arthroplasty (TKA). Design: Participants (n ​= ​60) were enrolled during routine physical therapy (PT) following TKA and randomized to the PAS intervention or an attention (ATT) control group. The PAS intervention included physical activity counseling and balance exercise to address joint loading symmetry; content was delivered during 2 sessions at the end of routine PT plus supplemental sessions 4-weeks and 8-weeks following PT. The ATT control condition included supplemental sessions at 4-weeks and 8-weeks focused on general evaluation of surgical recovery benchmarks. Primary outcomes were weekly minutes of moderate to vigorous physical activity (MVPA), measured with an accelerometer, and peak force loading symmetry (limb symmetry index; LSI) during a 10 ​m walk, measured with a 3-sensor in-shoe device. General linear mixed models compared changes in outcomes between randomized groups at 3-month and 6-month follow-up. Results: Both PAS and ATT groups increased MVPA, but there were no clinically meaningful between-group differences at 3- or 6-month follow-up (p ​> ​0.05). There were also no clinically meaningful between-group differences LSI at 3- or 6-month follow-up (p ​> ​0.05). Conclusion: The PAS intervention did not yield improvements beyond ATT control. It is possible that PAS components were being delivered as part of routine PT, and a more intensive intervention (e.g., more visits, guidance for exercise progression) or targeted approach (e.g., those with deficits at end of routine care) may be needed to further improve outcomes.